The Mystery of Iniquity : Melville as Poet, 1857-1891 - Shurr, William (Book collections on Project MUSE., 1972)
This book is the first to consider the work of Herman Melville's later years as a whole, in the light of his life and reading during those years and of the intellectual and artistic ambience of the later nineteenth century. With the exception of Billy Budd, almost all of the writing Melville produced between 1857 and 1891 is poetry. Until now little attention has been given to the poetry and it has been customary to view Melville's final masterpiece, Billy Budd, against the background of the earlier fiction -- almost as if the writing of the intervening thirty-four years had not existed. Will.